Cascaded exciton energy transfer in a monolayer semiconductor lateral heterostructure assisted by surface plasmon polariton - Shi, Jinwei (Nat Commun, 2017)
Atomically thin lateral heterostructures based on transition metal dichalcogenides have recently been demonstrated. In monolayer transition metal dichalcogenides, exciton energy transfer is typically limited to a short range (~1 μm), and additional losses may be incurred at the interfacial regions of a lateral heterostructure. To overcome these challenges, here we experimentally implement a planar metal-oxide-semiconductor structure by placing a WS(2)/MoS(2) monolayer heterostructure on top of an Al(2)O(3)-capped Ag single-crystalline plate. We find that the exciton energy transfer range can be extended to tens of microns in the hybrid structure mediated by an exciton-surface plasmon polariton–exciton conversion mechanism, allowing cascaded exciton energy transfer from one transition metal dichalcogenides region supporting high-energy exciton resonance to a different transition metal dichalcogenides region in the lateral heterostructure with low-energy exciton resonance. The realized planar hybrid structure combines two-dimensional light-emitting materials with planar plasmonic waveguides and offers great potential for developing integrated photonic and plasmonic devices.